Iowa Birdline update, October 31, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for October 31, 1994. Highlights of the update include sightings of White-winged Scoters, Black Scoters, a Lesser Black-backed Gull, a Hudsonian Godwit, a Laughing Gull, and Sandhill Cranes. The most evident migrants seen across the Iowa countryside were Red-tailed Hawks and Sparrows. Also included are handwritten notes for the next week's update with sightings of Scoters and Grebes. Epson - sheet feed/flatbed